How To Improve Financial Performance For Disable People Organizer? - Nur Siyami; Hesti Respatiningsih; Rizki Dewantara (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Financial problems can be avoided by understanding the importance of financial literacy as a basic need. In general, vulnerable groups, including people with disabilities, have a low level of financial literacy and are categorized as a low income group, so it is still difficult to gain access to financial institutions, products and services. Therefore, there is a need for on going multi-sectoral education and assistance so that business groups with disabilities are more financially literate so that they can increase their financial independence and deserve financial services. This research aims to examine the impact of Financial Literacy, Financial Inclusion and Financial Technology on the Financial Performance of DPO Restu Abadi Puworejo. Data collection techniques in this research were obtained by observation, interviews, questionnaires, documentation and literature study. The population in this study were members of the DPO Restu Abadi Purworejo. The sampling technique used was purposive sampling with the criteria for members who had joined for more than 3 years, had an active business for 2 years and had consistent business income for 1 year, resulting in a total sample of 8 people. The data analysis techniques in this research are Multiple Linear Regression, Determination Test, and Hypothesis Test (T Test and F Test). Multiple regression analysis produces the equation Y=a+bX1+bX2+e. The regression results show that financial literacy, financial inclusion and financial technology have an impact on increasing the financial performance of DPO Restu Abadi Purworejo.